La Lettera dei 138 (2006). Bilancio di un tentativo di dialogo non (del tutto) riuscito (Stato, Chiese e pluralismo confessionale, 2016)
Contributo sottoposto a valutazioneSOMMARIO: 1. Premessa - 2. La nascita della Lettera - 3. Contenuto della Lettera e commenti - 4. La (flebile) risposta della Santa Sede - 5. Conclusioni.ABSTRACT: The paper describes the birth of the “Common Word Between Us and You” initiative (2006) – also called “Letter of the 138” by the Italian commentators – its motives, contents and limits, and how it was welcomed by christian religious leaders and christian or lay scholars. It also aims to put a light on the meaning and possibilites of the interreligious dialogue between christian churches/denominations and religious leaders of the muslim majority countries.
Keywords: Varie